Peculiarities of the solid-state synthesis of yttrium and gadolinium orthovanadates raw material - Voloshyna, O.V.; Baumer, V.N.; Puzan, A.N.; Sidletskiy, O.Ts.; Gerasymov, Ia.V. (Functional Materials, 2015)
Present research deals with exploration of the kinetics of chemical interaction between yttrium or gadolinium oxide and vanadium (V) oxide. It was shown that in the temperature range up to 600°C the limiting stage of the orthovanadate synthesis is chemical interaction, and in the temperature range from 600°C to 800°C the limiting stage is diffusion of the starting oxide through the layer of the chemical interaction product. Optimal mode of the solid-state synthesis of the yttrium or gadolinium orthovanadates from the starting oxides was determined.